Penerapan Model Problem Based Learning untuk Meningkatkan Motivasi Belajar Siswa Kelas V dalam Pembelajaran Tematik di MI Semesta Mojokerto - Rahaju, Sumartini (MODELING: Jurnal Program Studi PGMI, 2023)
This article aims to find out how to increase the learning motivation of class V students in thematic learning at MI Semesta Mojokerto. The research method used is descriptive qualitative. Data collection in this research used observation instruments, interviews, questionnaires, and documentation and experimental methods. The subjects of this research were class V students, teachers (class V homeroom teachers) and school principals. This research was carried out at MI Semesta Mojokerto which is located in Kedungmaling Village, Sooko District, Mojokerto Regency. Problem Based Learning is a learning model which involves students trying to solve problems by going through several scientific stages. The learning steps include; a) presenting problems, b) organizing groups, c) searching for information, d) group discussions, e) preparing solutions, f) presenting solutions, g) reflection, h) improving critical and creative thinking skills. After implementing Problem Based Learning, changes in class student behavior at MI Semesta were visible during question-and-answer activities. Students did not hesitate when answering teacher questions, in discussion activities and making presentations, students were able to provide input, respond, be critical and the learning atmosphere becomes more enjoyable. The research results show that before implementing the Problem Based Learning learning model, the pre-test results for class V students averaged 43.2‰, whereas after implementing the Problem Based Learning learning model, learning motivation increased to an average of 84‰.